(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The Jadid Enlightenment movement, which emerged in the late 19th and early 20th centuries, played a pivotal role in modernizing education in Central Asia. This paper explores how integrative pedagogical approaches can enhance the teaching of Jadidist ideals in modern educational systems. The study focuses on blending traditional content with innovative methodologies, such as project-based learning, collaborative tasks, and digital storytelling, to foster critical thinking, creativity, and cultural identity development. Two groups of students (n=120) participated in a 10-week experimental study comparing traditional and integrative teaching methods. The results demonstrated that students exposed to integrative methods showed a significantly higher understanding of Jadidist ideals (85% vs. 65%), improved critical thinking skills (82% vs. 60%), and stronger cultural identity development (80% vs. 55%) compared to those taught using traditional methods. The findings suggest that integrative approaches not only engage students more deeply with historical content but also foster intellectual independence and cultural awareness. This paper concludes that adopting integrative methods in teaching historical and cultural topics like Jadidism can contribute to a more dynamic and meaningful learning experience.